Macroscopic infrared invisibility cloaking with wide viewing angles - Santosh Yadaw s/o Prabsankal (2017)
A macroscopic infrared invisibility cloak can hide any real-world object that is of centimeter size from being detected by the thermal detectors such as a FLIR thermal camera. A major limitation of current macroscopic infrared invisibility cloak designs via simplified transformation optics is that the cloak’s performance is limited to only a discrete number of viewing angles. In this Final Year Project, we have overcome this major limitation by successfully designing a macroscopic infrared invisibility cloak via paraxial optics. Our macroscopic infrared invisibility cloak consists of four identical thin prisms made of Zinc Sulphide that is capable of cloaking instantaneously a centimeter size real-world object from detection in the far infrared region by a thermal camera for continuous wide viewing angles of between ± 10⁰.